Dark papillary muscles sign in a patient with arrhythmogenic mitral valve prolapse: a case report - L. S. Evdokimova; I. E. Itskovich; A. V. Shakhbazyan (Российский кардиологический журнал, 2025)
Introduction. Recently, a subgroup of patients with mitral valve prolapse has been identified with an increased risk of ventricular arrhythmias and sudden cardiac death. One of the most characteristic signs of the arrhythmogenic mitral valve prolapse is mitral annular disjunction, detected by transthoracic or transesophageal echocardiography or by cardiac magnetic resonance imaging. Clinical and imaging data are used to stratify the risk of ventricular arrhythmias and determine patient management strategy.Case report. The article presents a case of a young man with arrhythmogenic mitral valve prolapse. The case demonstrates the anatomical features of mitral valve and related subvalvular structures, and also considers their impact on cardiac arrhythmias. Particular attention is paid to the description of mitral annular disjunction and dark papillary muscles sign.Conclusion. One of the tasks for imaging diagnostics in patients with ventricular arrhythmias and mitral valve prolapse is the assessment of phenotypic risk factors. Given the relationship of mitral annular disjunction with mitral valve prolapse, the development of mitral insufficiency and association with life-threatening ventricular arrhythmias, its timely diagnosis and follow-up of patients are extremely important.